Al-Hajj, Abdul Rahman. “The Qur’anic and Fiqhī Perspective on the Territorial Division of the World,” Year 12, Issue 45 (Summer 1427 AH/ 2006 CE), Pp. 65-94. - الحاج عبد الرحمن (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2006)
Abdul Rahman al-Hajj’s article focuses on the foundational construct of the traditional fiqh views of the territorial division of the world, attempting to capture the frames of reference on which these views are based, and how they relate to the textual frame of reference in an effort to highlight the general Qur'anic conception of the inhabited earth. It discusses the historical and doctrinal frames of reference for the traditional fiqh conceptions of the territorial division of the earth, and argues that these conceptions lack a textual basis from the Qur'an and the Sunnah. It examines textual, historical, and doctrinal frames of reference, and discourses on the geographic world, and concludes with a summary of the Qur’anic conception of the geography of the world.